The European Language Portfolio in Irish post-primary education: a longitudinal empirical evaluation - Sisamakis, Emmanouil M. (Trinity College (Dublin, Ireland). Centre for Language and Communication Studies, 2006)
This thesis is a longitudinal examination of how the introduction of the Council of Europe's European Language Portfolio (ELP) has affected foreign/second language teaching and learning in Irish post-primary schools. It examines and evaluates the nature and implications of the experience of a number of teachers and learners who use the ELP in their classes. Chapter 1 sketches the European background of the ELP by presenting a brief overview of related issues, the Council of Europe and the policies it pursues as regards language education and the related projects it has organised. It then explains how the ELP was developed and piloted, and summarises current developments related to its successful implementation, dissemination and evaluation. The chapter also refers to the importance the ELP seems to have assumed on the agenda of policy makers outside the CoE, such as the European Union. The chapter goes on to provide an overview of the Common European Framework of Reference for Languages (CEF), offers a brief examination of the claims made h various publications concerning the effects the CEF/ELP can have on language education, and presents some of the most comprehensive attempts made so far towards an 'ELP-oriented pedagogy'. Finally, it presents the case for an in-depth longitudinal quantitative and qualitative exploration of whether the ELP actively promotes what it claims to promote, under which prerequisites, and how it works when superimposed on the FL/SL curricula currently in place. Chapter 2 discusses Irish post-primary language education, for which the ELP model in question was developed as a product of the 'Learner Autonomy Project' (LAP), and presents the main features of the LAP, the principal design features of this model and the work of the ELP Support Network (ELP SN) which offers on-going support to teachers using the ELP in Irish post-primary education. It also summarizes the findings of the predecessor of the current longitudinal project, the six-month ELP empirical evaluation project, conducted through the ELP SN. Finally, it presents an overview of self-determination theory, which supplemented the theoretical outlook, research methods and instruments of this project, and presents the theoretical background to this project. In Chapter 3, the rationale, methodology, environment, limitations and expected outcomes of the research project are discussed in some depth. Options followed related to the data elicitation instruments, confidentiality issues, and extended triangulation techniques are examined in considerable detail. Chapters 4 and 5 present and critically examine the project findings. Chapter 4 presents and examines summative project findings, while Chapter 5 discusses class- and teacher-specific findings. These two chapters draw from and should be read in tandem with the extensive data-containing appendices of the thesis, which exceed five thousand pages. This arrangement was employed since the large number and elaborate nature of the data elicitation instruments resulted in 'raw data' exceeding five thousand pages after a first 'data-reducing' codification of responses. As a result, it would be all but impossible to discuss the totality of the data in any meaningful way in the space available. At the same time, transparency and objectivity are best served by the current arrangement, where both the full recoded responses appear appended for the interested reader to peruse at leisure, and a critical analysis and discussion of the findings appears in the main body of the thesis, focusing on the themes which come out of the findings as most prominent and/or statistically significant. Chapter 6 offers a brief summary of the principal conclusions which can be reached on the basis of the project findings, and examines how these conclusions may inform language provision in Irish post-primary education as well as in other language learning settings. First, it examines what the project participants' (teachers' and learners') responses tell us about this specific ELP model, the curricula currently in place, their schools, the practices they followed in project classes, their teachers/students, and themselves. Then it briefly addresses the issue of whole-school development and the potential benefits of advocating an ELP-informed pedagogy and introducing portfoliobased learning and benchmarking in all subjects and not only FL teaching and learning. Next, it discusses the implications of the possible introduction of Content and Language Integrated Learning in post-primary education along with the ELP in response to some of the concerns raised by the project participants. Finally, it examines what the findings of this project may have to offer to similar projects and ELP development, implementation and evaluation conducted in settings other than Irish post-primary education.
Keywords: Applied Linguistics, Ph.D.; Ph.D. Trinity College Dublin